Nilai Toleransi pada Bingkai Kebijakan Dalam dan Luar Negeri UAE - Alim, Muhamad; Akbar, Alwi; Muttaqin, Mochammad Izdiyan (Jurnal ICMES, 2023)
Starting at the end of the 20th century, the United Arab Emirates (UAE) began to focus its policies on forming a national identity because the migrant population dominated the local population. To overcome this phenomenon, increase investment and economic growth, and maintain domestic harmonization, the UAE government is trying to shape a national identity and implement the value of tolerance in its domestic and foreign policies. This article will describe how the UAE uses tolerance to form a national identity in its domestic and foreign policies and how the Islamic religion plays a role. This research uses qualitative methods and the concept of constructivism in foreign policy. The study finds that the UAE has implemented several approaches to create a national identity full of tolerance to achieve its national interests, namely investment, economic growth, the tourism industry and regional security.